Textile Materials and Structures with Negative Poisson's Ratio - An Overview (Journal of Fiber Bioengineering and Informatics, 2013)
Material with negative Poisson's ratio is a kind of new structural material with special physical propertiesand geometric structure, which undergoes a transverse expansion when stretched in longitudinal directionand a transverse contraction when compressed. Compared with common textile materials, auxetictextile materials are significantly different in terms of thier structures and properties. Thereof, reviewson auxetic materials of foam, polymer and textile materials were investigated, and the mechanismof the dilation property was analyzed and obtained in this paper. It is found that these auxeticmaterials are dependent on the microstructures with reentrant structures or rotating structures. Theanalysis of the structure of materials with negative Poisson's ratio can contribute to the new textilematerial technology and new functional textile products, such as magnetic-shielding fabrics and water-repellent/wind-proof fabrics. It is also helpful in infrastructure, aerospace engineering, biomedicalengineering and environmental engineering.
Keywords: Negative Poisson's Ratio; Fabric; Fibre; Polymer; Foam